Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, Ta có : \(x=\sqrt{3+2\sqrt{2}}+\sqrt{11-6\sqrt{2}}\)
\(=\sqrt{\left(\sqrt{2}+1\right)^2}+\sqrt{\left(3-\sqrt{2}\right)^2}=4\)
Thay x = 4 => \(\sqrt{x}=2\) vào B ta được :
\(B=\frac{2+5}{2-3}=-7\)
b, Ta có : Với \(x\ge0;x\ne9\)
\(A=\frac{4}{\sqrt{x}+3}+\frac{2x-\sqrt{x}-13}{x-9}-\frac{\sqrt{x}}{\sqrt{x}-3}\)
\(=\frac{4\left(\sqrt{x}-3\right)+2x-\sqrt{x}-13-\sqrt{x}\left(\sqrt{x}+3\right)}{x-9}\)
\(=\frac{4\sqrt{x}-12+2x-\sqrt{x}-13-x-3\sqrt{x}}{x-9}=\frac{x-25}{x-9}\)
Lại có \(P=\frac{A}{B}\Rightarrow P=\frac{\frac{x-25}{x-9}}{\frac{\sqrt{x}+5}{\sqrt{x}-3}}=\frac{\sqrt{x}-5}{\sqrt{x}+3}\)
a) ĐK: \(x\ge0;x\ne1\)
Ta có: \(x-1=\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)\)
\(x+\sqrt{x}-2=\left(x-1\right)+\left(\sqrt{x}-1\right)=\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)\)
=> \(P=\frac{3\left(\sqrt{x}+1\right)+\sqrt{x}-3}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}:\frac{x+2-\sqrt{x}\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{4\sqrt{x}}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}:\frac{2+\sqrt{x}}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{4\sqrt{x}}{\sqrt{x}+1}\)
b) \(P=\sqrt{x}-1\)
<=> \(\frac{4\sqrt{x}}{\sqrt{x}+1}=\sqrt{x}-1\)
<=> \(x-4\sqrt{x}-1=0\)
<=> \(\orbr{\begin{cases}\sqrt{x}=2+\sqrt{5}\\\sqrt{x}=2-\sqrt{5}< 0\left(loại\right)\end{cases}}\)
<=> \(x=9+4\sqrt{5}\)thỏa mãn
a/ \(A=\left(\frac{2\sqrt{x}+x}{\sqrt{x}^3-1}-\frac{1}{\sqrt{x}-1}\right):\frac{\sqrt{x}+2}{x+\sqrt{x}+1}\)
\(=\left[\frac{2\sqrt{x}+x}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}-\frac{1}{\sqrt{x}-1}\right]:\frac{\sqrt{x}+2}{x+\sqrt{x}+1}\)
\(=\frac{2\sqrt{x}+x-x-\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}.\frac{x+\sqrt{x}+1}{\sqrt{x}+2}\)
\(=\frac{\sqrt{x}-1}{\sqrt{x}-1}.\frac{1}{\sqrt{x}+2}=\frac{1}{\sqrt{x}+2}\)
b/ Thay \(x=4+2\sqrt{3}\) vào A ta được:
\(A=\frac{1}{\sqrt{4+2\sqrt{3}}+2}=\frac{1}{\sqrt{\left(\sqrt{3}+1\right)^2}+2}=\frac{1}{\sqrt{3}+3}\)
\(\Rightarrow\sqrt{A}=\frac{1}{\sqrt{\sqrt{3}+3}}\)
a) \(\sqrt{x-1-2\sqrt{x-2}}=\sqrt{\left(x-2\right)-2\sqrt{x-2}+1}=\sqrt{\left(\sqrt{x-2}-1\right)^2}=\left|\sqrt{x-2}-1\right|\)
b) \(\sqrt{x-2+2\sqrt{x-3}}-\sqrt{x-3}\)
\(=\sqrt{\left(x-3\right)+2\sqrt{x-3}+1}-\sqrt{x-3}\)
\(=\sqrt{\left(\sqrt{x-3}+1\right)^2}-\sqrt{x-3}=\sqrt{x-3}+1-\sqrt{x-3}=1\)